THE EFFECT OF CRM (CUSTOMER RELATIONSHIP MARKETING) AND BRAND IMAGE ON CUSTOMER LOYALTY: A CASE STUDY OF AULIA TOOTHPICK CHIPS IN JAMBI CITY - Pangestu, Mira Gustiana; Ingriana, Alberta; Yossinomita, Yossinomita; Feranika, Ayu (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
Abstract This study to analyze the influence of Customer Relationship Marketing and Brand Image on Consumer Loyalty at Aulia Toothpick Chips in Jambi City. This study employed a quantitative method involving 120 respondents selected using random sampling. Data were collected via a questionnaire using a Likert scale and analyzed using multiple linear regression. The results indicate that, collectively, Customer Relationship Marketing and Brand Image have a significant effect on Consumer Loyalty, with a coefficient of determination (R²) of 60.3%. The remaining 39.7% is influenced by other factors not discussed in this study. Partially, Customer Relationship Management (CRM) has a positive and significant effect on Consumer Loyalty. This is evidenced by the t-test, which shows a significance value for the CRM variable of 0.001 < 0.05. Furthermore, Brand Image has a significant effect on Consumer Loyalty. Meanwhile, the results of the F-test, which showed a significance value of 0.000 < 0.05. Keywords: Customer Relationship Marketing, Brand Image,Customer loyalty,MSMe